Strong ALK and PD-L1 positive IHC expression related ALK amplification in an advanced lung sarcomatoid carcinoma: A therapeutic trap?. (February 2021) - Gendarme, Sébastien; Matton, Lise; Antoine, Martine; Kerrou, Khaldoun; Ruppert, Anne-Marie; Epaud, Christelle; Cadranel, Jacques; Fallet, Vincent
Highlights: Lung sarcomatoid carcinoma is a rare tumor with high mutations rates. We should pay attention to IHC positive results for ALK in case of unusual phenotype. Our case suggests alectinib resistance to ALK-amplified tumors. Our case reports the first case of efficacy of immunotherapy in ALK-amplified tumors. Abstract: Objectives: Immunohistochemistry (IHC) is considered as a screening method for ALK rearrangement thanks to its excellent sensitivity. Strong marking on immunohistochemistry give the go-ahead to start ALK tyrosine kinase inhibitors (ALK TKI). Lack of therapeutic response may then lead to the suspicion of molecular alterations other than ALK rearrangements. Methods: We present a patient with strong ALK and PD-L1 positive IHC expression lung sarcomatoid carcinoma with initial life-threatening disease progression after beginning ALK TKI. We also review the literature to summarize ALK amplification clinical features and therapeutic management in lung cancers. Results: Fluorescence in situ Hybridization (FISH) revealed ALK amplification on the initial anatomopathological samples. Lack of ALK rearrangement and strong PD-L1 positive IHC expression led to the initiation of immune checkpoint inhibitor (ICI) as a second line of treatment, with an excellent response. Conclusion: We demonstrated that IHC positive test, in these cases, must be interpreted with caution. FISH analysis has to be recommended to confirm IHC results in case of unusual phenotype, such as smoker or lung cancer other than adenocarcinoma. Although lung carcinoma with ALK rearrangement seems to be not sensitive to ICI, further investigations should be conducted on other types of ALK molecular alterations. ALK amplifications, as observed in the present case, should not be an impediment to taking into account the PD-L1 marking for the initiation of treatment by immunotherapy.